CAP Analysis of the Distribution of the Introduced Bemisia tabaci (Hemiptera: Aleyrodidae) Species Complex in Xinjiang, China and the Southerly Expansion of the Mediterranean Species. Issue 2 (12th April 2021) - Jia, Zunzun; Fu, Kaiyun; Guo, Wenchao; Jiang, Weihua; Ahmat, Tursun; Ding, Xinhua; He, Jiang; Wang, Xiaowu
Abstract: Bemisia tabaci (Gennadius) cryptic complex has invaded Xinjiang, China, since 1998. The distribution of Mediterranean (MED) and Middle East-Asia Minor 1 (MEAM1) B. tabaci substrains has been gradually identified due to the development of molecular technology. In this study, the distribution of MED and MEAM1 in Xinjiang was determined by cleaved amplified polymorphic sequence (CAPs). Results showed that MED dominated in northern Xinjiang (84%), whereas MEAM1 was dominant in southern Xinjiang (72%). Five pairs of simple sequence repeat (SSR) primers were used to analyze the genetic diversity of B. tabaci among 36 geographic populations. The genetic diversity of MED and MEAM1was low and varied little among populations in Xinjiang (0.09 ± 0.14 and 0.09 ± 0.13, respectively). Based on ∆ K statistic, 13 populations of MEAM1 could be classified into two subgroups at K = 2, whereas the 23 populations of MED could be classified into four subgroups at K = 4. However, Mantel t -test demonstrated no correlation between geographical and genetic distances among B. tabaci complex ( R = 0.42, P = 1.00). Neighbor-joining and principal coordinate analysis showed that geographical isolation and interspecific differences were the main causes of the genetic variation. Gene flow predicted that MEAM1 was most likely introduced from Urumqi to the southern Xinjiang. Meanwhile, a large proportion of MED in Kashi region came from Changji and Yining. To block ongoing dispersal, strict detection and flower quarantine regulations need to be enforced.